Erupted Compound Odontoma Associated with Missing Tooth: A Rare Case Report - Tantanapornkul, Weeraya; Kaomongkolgit, Ruchadaporn; Tohnak, Sirilawan; Promma, Lalitkorn; Chantarangsu, Soranan (Journal of Dentistry Indonesia, 2020)
Odontomas are one of the most frequently found odontogenic tumors that consist of dental tissues. Odontomas have been classified into two types: compound and complex odontomas. They are usually discovered on routine radiographic examination. In rare cases, the odontoma erupt into the oral cavity, called an erupted odontoma. The first case was published in 1980, and since then, there have been not more than 50 cases being reported in the literature. Most of the reported cases are erupted complex odontoma. This case report represents a rare case of an erupted compound odontoma in a young patient who came with the complaint of esthetics in the lower left posterior teeth.